Suramin Alleviates Glomerular Injury and Inflammation in the Remnant Kidney - Liu, Na; He, Song; Tolbert, Evelyn; Gong, Rujun; Bayliss, George; Zhuang, Shougang (PLOS ONE, 2012)
Background Recently, we demonstrated that suramin, a compound that inhibits the interaction of multiple cytokines/growth factors with their receptors, inhibits activation and proliferation of renal interstitial fibroblasts, and attenuates the development of renal interstitial fibrosis in the murine model of unilateral ureteral obstruction (UUO). However, it remains unclear whether suramin can alleviate glomerular and vascular lesions, which are not typical pathological changes in the UUO model. So we tested the efficacy of suramin in the remnant kidney after 5/6 nephrectomy, a model characterized by the slow development of glomerulosclerosis, vascular sclerosis, tubulointerstitial fibrosis and renal inflammation, mimicking human disease. Methods/Findings 5/6 of normal renal mass was surgically ablated in male rats. On the second week after surgery, rats were randomly divided into suramin treatment and non-treatment groups. Suramin was given at 10 mg/kg once per week for two weeks. In the remnant kidney of mice receiving suramin, glomerulosclerosis and vascular sclerosis as well as inflammation were ameliorated. Suramin also attenuated tubular expression of two chemokines, monocyte chemoattractant protein-1 and regulated upon expression normal T cell expressed and secreted (RANTES). After renal mass ablation, several intracellular molecules associated with renal fibrosis, including NF-kappaB p65, Smad-3, signal transducer and activator of transcription-3 and extracellular regulated kinase 1/2, are phosphorylated; suramin treatment inhibited their phosphorylation. Futhermore, suramin abolished renal ablation-induced phosphorylation of epidermal growth factor receptor and platelet derived growth factor receptor, two receptors that mediate renal fibrosis. Conclusions and Significance These findings suggest that suramin attenuates glomerular and vascular injury and reduces inflammatory responses by suppression of multiple growth factor receptor-mediated profibrotic signaling pathways. Therefore, suramin may be a useful drug in preventing the fibrosis and sclerosis that characterizes progression of chronic kidney disease.